The Value of Voice to Managers: Employee Identification and the Content of Voice - Burris, Ethan R.; Rockmann, Kevin W.; Kimmons, Yurianna S. (Academy of Management Journal, 2017)
Previous research on employee voice has aimed to understand the antecedents and outcomes of the frequency of speaking up. Yet, how these antecedents translate into outcomes may depend on what employees speak up about and its implications for implementation. We engage in three studies to explore what individuals speak up about, why they speak up about those things, and the consequences of voicing such content. First, through a qualitative field study, we find evidence for three dimensions of voice content: the importance of initiating change, the required resources to enact the desired change, and the interdependencies involved in implementing the desired change. Further, specific targets of identification—either one’s local work unit or one’s broader profession—shape whether the issues individuals raise take into account barriers related to resources and interdependencies. Next, in a quantitative field study, we find that voicing on issues related to one’s work unit or profession mediates the relationship between employee identification and managers’ valuation of voice. Finally, in an experiment, we manipulate importance, resources, and interdependencies of implementation and find these dimensions of voice content influence managerial value of voice. These results offer meaningful theoretical implications for the literatures on employee voice and identification.